POTENSI WISATA KAMPUNG PELANGI SEBAGAI DAYA TARIK WISATA - Yuniarto Rahmad Satato; Henry Yuliamir; Eni Rahayu (STEKOM PRESS, 2022)
The tourist attraction is one important element in the world of tourism. Tourist objects and attractions can be natural, cultural, man-made, living arrangements and so on that have attractions and selling oints to be visited or enjoyed by tourists. In this study, the rainbow village is one of the artificial tours in the city of Semarang that must meet the 4A tourism component, namely Attractions, Accessibility, Amity, Ancillary. The purpose of this study was to determine the development of the 4A Tourism Components of Rainbow Village tourism as an artificial tour in the city of Semarang. This study uses a qualitative method with 9 respondents. Data collection techniques using interview, observation and documentation. The analysis uses data processing from the data findings and is developed to get conclusions.The results showed that the rainbow village fulfilled the 4A tourism component. It also found how to manage development efforts and provided suggestions for completion.